2017
DOI: 10.1042/etls20170058
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of the microbiota member Bifidobacterium in modulating immune-linked diseases

Abstract: The gut-associated microbiota is essential for multiple physiological processes, including immune development. Acquisition of our initial pioneer microbial communities, including the dominant early life genus Bifidobacterium, occurs at a critical period of immune maturation and programming. Bifidobacteria are resident microbiota members throughout our lifetime and have been shown to modulate specific immune cells and pathways. Notably, reductions in this genus have been associated with several diseases, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 106 publications
(115 reference statements)
0
67
0
1
Order By: Relevance
“…Our previous studies demonstrated an important role for infant-associated Bifidobacterium breve, which reduced pathological cell shedding processes in adult mice via the bifidobacterial exopolysaccharide capsule and host MyD88 signalling interactions [16,28]. Although Bifidobacterium is found at high levels in infants, species and strains of this genus are not consistently detected in neonatal mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated an important role for infant-associated Bifidobacterium breve, which reduced pathological cell shedding processes in adult mice via the bifidobacterial exopolysaccharide capsule and host MyD88 signalling interactions [16,28]. Although Bifidobacterium is found at high levels in infants, species and strains of this genus are not consistently detected in neonatal mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated an important role for infant‐associated Bifidobacterium breve, which reduced pathological cell shedding processes in adult mice via the bifidobacterial exopolysaccharide capsule and host MyD88 signaling interactions 17,35 . Although Bifidobacterium is found at high levels in infants, species and strains of this genus are not consistently detected in neonatal mice.…”
Section: Discussionmentioning
confidence: 99%
“…The early-life developmental window represents a critical time for microbe-host interactions as this is when foundations for future health and well-being are established. Colonisation of pioneer microbes shortly after birth represents a key first step in this mutualistic relationship; shaping the developing microbial community, and in turn impacting numerous host physiological processes [1][2][3][4][5]. Although the microbiota of adults is complex in nature, the gastrointestinal (GI) tract of full-term healthy infants is relatively simplistic, dominated by the genus Bifidobacterium that can persist into early childhood [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the microbiota of adults is complex in nature, the gastrointestinal (GI) tract of full-term healthy infants is relatively simplistic, dominated by the genus Bifidobacterium that can persist into early childhood [3,6]. In the first months of birth, the loss of Bifidobacterium species or gain of other bacteria during this critical window of opportunity, may significantly alter the 'natural' progression of the microbial community that may lead to a variety of negative consequences for host health including a predisposition to autoimmune/metabolic diseases (like allergies and childhood obesity) [1,2].…”
Section: Introductionmentioning
confidence: 99%